2015
DOI: 10.5430/ijhe.v4n2p116
|View full text |Cite
|
Sign up to set email alerts
|

The Tail Wagging the Dog; An Overdue Examination of Student Teaching Evaluations

Abstract: Purpose: The purpose of this research is to examine the impact of several factors beyond the professor's control and their unique impact on Student Teaching Evaluations (STEs). The present research pulls together a substantial amount of data to statistically analyze several academic historical legends about just how vulnerable STEs are to the effects of: class size, course type, professor gender, and course grades.Design/methodology/approach: This research is utilizes over 30,000 individual student evaluations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Effective mentoring can be difficult to measure as it involves both metrics of graduate student success (e.g., publishing papers, progress toward graduation), and less tangible metrics such as student mental health, support, and satisfaction. Additionally, evidence from research on teaching evaluations suggests that students can be biased when evaluating certain groups, such as women, and thus evaluations based on student opinion alone must be used with caution (Boring, ; Mengel, Zölitz, & Mengel, ; Miles & House, ; Stark & Freishtat, ; Storage, Horne, Cimpian, & Leslie, ). Finally, finding mechanisms that allow for honest feedback in academia is challenging, as graduate students and postdocs must be protected from retribution in cases of a negative review.…”
Section: The Way Forward: a Model For Improving Mentorship In Stemmentioning
confidence: 99%
“…Effective mentoring can be difficult to measure as it involves both metrics of graduate student success (e.g., publishing papers, progress toward graduation), and less tangible metrics such as student mental health, support, and satisfaction. Additionally, evidence from research on teaching evaluations suggests that students can be biased when evaluating certain groups, such as women, and thus evaluations based on student opinion alone must be used with caution (Boring, ; Mengel, Zölitz, & Mengel, ; Miles & House, ; Stark & Freishtat, ; Storage, Horne, Cimpian, & Leslie, ). Finally, finding mechanisms that allow for honest feedback in academia is challenging, as graduate students and postdocs must be protected from retribution in cases of a negative review.…”
Section: The Way Forward: a Model For Improving Mentorship In Stemmentioning
confidence: 99%
“…Ratings should be completed anonymously without the teacher present and be standardized in administration (e.g., identical instructions, same time frame for administration) across all courses in the school. Individuals and committees interpreting the ratings should understand variables that might affect student evaluations such as motivation for taking the course, workload in the course, timing of the evaluations, level of the student and course, class size, and other variables . Too few faculty are knowledgeable about variables that can influence student ratings in their courses.…”
Section: Using Student Evaluations For Personnel Decisionsmentioning
confidence: 99%
“…They hypothesize that when students expected they would get better grades, they would give teachers higher teaching evaluation scores. Miles and House (2015) examined the impact of factors that teachers can't control on teaching evaluation scores. The results found that higher student' expected grades may lead to higher teaching evaluation scores.…”
Section: Literature Reviewmentioning
confidence: 99%